Interconnectivity Explains High Canalicular Network Robustness between Neighboring Osteocyte Lacunae in Human Bone. Issue 4 (29th December 2021) - Bortel, Emely; Grover, Liam M; Eisenstein, Neil; Seim, Christian; Suhonen, Heikki; Pacureanu, Alexandra; Westenberger, Peter; Raum, Kay; Langer, Max; Peyrin, Francoise; Addison, Owen; Hesse, Bernhard
Abstract : Osteocytes are the most frequent bone cells connected with each other through cell processes within tiny tubular‐shaped canaliculi. The so‐called osteocyte lacunar‐canalicular network (LCN) plays a crucial role in bone remodeling and mineral homeostasis. Given the critical nature of these functions, it is herein hypothesized that the LCN must be structurally "overengineered" to provide network resilience. This hypothesis is tested by characterizing canalicular networks in human bone at the fundamental "building‐block" level of LCN formed by two adjacent osteocytes. As the hierarchical micro‐ and macroscale structure of bone is influenced by anatomical location, subjected loads, and growth rate, three distinct tissue types are studied. These include femur, jaw, and heterotopic ossification (HO), a rapidly forming mineralized tissue found in soft tissue compartments following severe trauma. It is found that the LCNs at the fundamental level are composed of hundreds of canalicular segments but of only few separated groups of linked canaliculi (canalicular clusters), resulting in a strongly pronounced interconnectivity. Fluid permeability simulations on intact and artificially altered LCN suggest that the function of the LCN is not only to optimize rapid and efficient access to bone mineral, but also to maintain high permeability when inevitable local interruption of canaliculi occurs. Abstract : This study reports that the human bone lacunar‐canalicular networks formed by two neighboring osteocytes are composed of hundreds of canalicular segments but of only few separated groups of linked canaliculi (canalicular clusters), resulting in a strongly pronounced interconnectivity. This interconnectivity enables robust fluid permeability and access to bone mineral after local interruption of individual canaliculi.